(untitled) (Web of Teachers: Inderscience Research, 2025)
Cardiovascular diseases (CVDs) remain a leading cause of morbidity and mortality worldwide, with factors such as atherosclerosis, hypertension, and heart failure contributing to the burden. A growing body of evidence has highlighted the critical role of diet in the prevention, management, and treatment of cardiovascular diseases. The influence of dietary patterns on heart health is multifaceted, involving mechanisms such as inflammation, lipid metabolism, oxidative stress, and endothelial function. This paper reviews the pathophysiological mechanisms of cardiovascular diseases and examines how dietary interventions can modify these mechanisms to improve outcomes in patients with CVDs. The paper also explores specific dietary strategies, including the Mediterranean diet, DASH (Dietary Approaches to Stop Hypertension), and plant-based diets, that have been shown to reduce the risk and severity of cardiovascular conditions.